A new role for monomeric ParA/Soj in chromosome dynamics in Bacillus subtilis. Issue 1 (16th January 2023) - Roberts, David M.
Abstract: ParABS (Soj‐Spo0J) systems were initially implicated in plasmid and chromosome segregation in bacteria. However, it is now increasingly understood that they play multiple roles in cell cycle events in Bacillus subtilis, and possibly other bacteria. In a recent study, monomeric forms of ParA/Soj have been implicated in regulating aspects of chromosome dynamics during B. subtilis sporulation. In this commentary, I will discuss the known roles of ParABS systems, explore why sporulation is a valuable model for studying these proteins, and the new insights into the role of monomeric ParA/Soj. Finally, I will touch upon some of the future work that remains. Abstract : ParABS (Soj‐Spo0J) systems and SMC complexes are critical mediators of chromosome dynamics in a range of bacteria. In this commentary, I review the roles of these systems in Bacillus subtilis, as well as discuss a recent study that implicates a monomeric variant of ParA/Soj as a novel regulator of SMC release and redistribution after loading onto the DNA, a process that is critical for chromosome reorganization during axial filament formation in early sporulation.